Behavioral Health Screening in Pediatric Primary Care: A Pilot Study. (July 2015) - Valleley, Rachel J.; Romer, Natalie; Kupzyk, Sara; Evans, Joseph H.; Allen, Keith D.
This pilot study investigated the effect of the Pediatric Symptom Checklist (PSC) on identification of and physician response to behavioral health (BH) concerns. Researchers reviewed 1211 charts of youth aged 4 to 16 years. Records were compared during baseline and an intervention consisting of implementation of the PSC to determine the rate of BH identification and pediatrician response. Access to PSC data resulted in a trivial difference in BH concerns identified by physicians and did not affect physician responses. This case study demonstrates that simply implementing BH screening in primary care may not result in improved outcomes for these children.